Incidence of Nephrogenic Systemic Fibrosis Using Gadobenate Dimeglumine in 1423 Patients With Renal Insufficiency Compared With Gadodiamide. Issue 11 (November 2016) - Bruce, Richard; Wentland, Andrew L.; Haemel, Anna K.; Garrett, Robert W.; Sadowski, Donna R.; Djamali, Arjang; Sadowski, Elizabeth A.
Abstract : Objective: The purpose of this study was to assess the incidence of nephrogenic systemic fibrosis (NSF) before and after educational interventions, implementation of a clinical screening process, and change to gadobenate dimeglumine in patients who had an estimated glomerular filtration rate (eGFR) of 30 mL/min per 1.72 m 2 or less. Methods: This is a Health Insurance Portability and Accountability Act compliant, institutional review board exempt study. Two periods were studied—July 2005 to June 2006, during which gadodiamide was utilized as our magnetic resonance (MR) contrast agent, and November 2006 to August 2014, during which gadobenate dimeglumine was used as our MR contrast agent in patients who had an eGFR 30 mL/min per 1.72 m 2 or less. In addition to a change in the MR contrast agent, education of our staff physician to the risks of NSF with MR contrast agents and the implementation of a clinical screening process occurred. The rate of NSF before and after the interventions was compared using the χ 2 test. Results: There was a statistically significant difference in the incidence of NSF in patients with an eGFR 30 mL/min per 1.72 m 2 or less between the 2 periods: July 2005 to June 2006, 6 of 246 patients were diagnosed with NSF ( P < 0.001), versus November 2006 to August 2014, 0 of 1423 patients were diagnosed with NSF. Conclusions: Our data demonstrates a marked decrease in the incidence of NSF after education of our referring physicians, implementation of clinical screening process, and change to gadobenate dimeglumine from gadodiamide in patients with renal insufficiency. This approach potentially provides an acceptable risk-benefit profile for patients with renal insufficiency that required MR imaging for clinical care.